Plasmonic Amyloid Tactoids. Issue 51 (17th October 2021) - Yuan, Ye; Almohammadi, Hamed; Probst, Julie; Mezzenga, Raffaele
Abstract: Despite their link to neurodegenerative diseases, amyloids of natural and synthetic sources can also serve as building blocks for functional materials, while possessing intrinsic photonic properties. Here, it is demonstrated that orientationally ordered amyloid fibrils exhibit polarization‐dependent fluorescence, and can mechanically align rod‐shaped plasmonic nanoparticles codispersed with them. The coupling between the photonic fibrils in liquid crystalline phases and the plasmonic effect of the nanoparticles leads to selective activation of plasmonic extinctions as well as enhanced fluorescence from the hybrid material. These findings are consistent with numerical simulations of the near‐field plasmonic enhancement around the nanoparticles. The study provides an approach to synthesize the intrinsic photonic and mechanical properties of amyloid into functional hybrid materials, and may help improve the detection of amyloid deposits based on their enhanced intrinsic luminescence. Abstract : Hybrid liquid crystalline tactoids consisting of gold nanorods aligned by amyloid fibrils exhibit enhanced fluorescence with polarization and wavelength sensitivity. This work demonstrates how anisotropic colloidal self‐assembly couples plasmonic nanoparticles with the intrinsic photonical properties of amyloids.